2021
DOI: 10.1155/2021/5792975
|View full text |Cite
|
Sign up to set email alerts
|

SOSPCNN: Structurally Optimized Stochastic Pooling Convolutional Neural Network for Tetralogy of Fallot Recognition

Abstract: Aim. This study proposes a new artificial intelligence model based on cardiovascular computed tomography for more efficient and precise recognition of Tetralogy of Fallot (TOF). Methods. Our model is a structurally optimized stochastic pooling convolutional neural network (SOSPCNN), which combines stochastic pooling, structural optimization, and convolutional neural network. In addition, multiple-way data augmentation is used to overcome overfitting. Grad-CAM is employed to provide explainability to the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The results of deep learning [20] rely on data, and a large amount of simulation data provides the possibility of applying deep learning to image denoising. This is especially true for images with complex backgrounds, where traditional algorithms often do not yield good results even after a lot of effort [21].…”
Section: Application Of Cnn In Image Denoisingmentioning
confidence: 99%
“…The results of deep learning [20] rely on data, and a large amount of simulation data provides the possibility of applying deep learning to image denoising. This is especially true for images with complex backgrounds, where traditional algorithms often do not yield good results even after a lot of effort [21].…”
Section: Application Of Cnn In Image Denoisingmentioning
confidence: 99%
“…They can do an excellent job of image extraction. It has been found that they can be used not only for image classification tasks but also for backbone architectures in more complex object detection tasks [43][44][45][46][47].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…L. Fernandes & Bala, 2016;S. L. Fernandes & Jha, 2020;ORTIZ et al, 2021;Wang et al, 2021). Quantum machine learning-based diagnosis systems are also gaining increased intention (Umer et al, n.d.).…”
Section: Quantum Computing Conceptsmentioning
confidence: 99%